Beyond Juvenile Delinquency: Youth Involvement as Perpetrators of Criminality - Fernando, Henky; Abdullah, Irwan; Larasati, Yuniar Galuh; Novarizal, Riky; Morin, Leanne (Universitas Andalas, 2024)
Adolescents' involvement as perpetrators of criminality in Indonesia has gone beyond the patterns of deviant behavior and actions categorized as juvenile delinquency. Adolescents' involvement as perpetrators of criminality has not been given much scientific attention in previous studies. This study focuses on the question,